2006
DOI: 10.1186/1471-2229-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Storage protein profiles in Spanish and runner market type peanuts and potential markers

Abstract: Background: Proteomic analysis has proven to be the most powerful method for describing plant species and lines, and for identification of proteins in complex mixtures. The strength of this method resides in high resolving power of two-dimensional electrophoresis (2-DE), coupled with highly sensitive mass spectrometry (MS), and sequence homology search. By using this method, we might find polymorphic markers to differentiate peanut subspecies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…In proteomic analysis of storage protein profiles in peanuts [12], total protein was extracted using a modified TCA/acetone precipitation protocol with the first step of de-fatting using hexane. Dry peanut kernels were frozen in liquid N 2 and ground to powder in a mill and defatted with hexane (10 mL/g dry weight) at -208C overnight.…”
Section: Legume Seedsmentioning
confidence: 99%
See 2 more Smart Citations
“…In proteomic analysis of storage protein profiles in peanuts [12], total protein was extracted using a modified TCA/acetone precipitation protocol with the first step of de-fatting using hexane. Dry peanut kernels were frozen in liquid N 2 and ground to powder in a mill and defatted with hexane (10 mL/g dry weight) at -208C overnight.…”
Section: Legume Seedsmentioning
confidence: 99%
“…Examples of protein extraction from recalcitrant plant tissues for proteomic analysis Protein extraction protocols Species, tissues, and references TCA/acetone precipitation C. sativa roots [20], maize seeds [64] and roots [13], M. truncatula seeds [65] and roots [69], peanut seeds [12], olive seeds [66], soybean seed [68], wheat leaf [31], olive leaf [28], rice sheath [16] and internode [17], grape berry cluster [40] and mesocarp [72], fruits (banana, apple, strawberry) [38,39,61], potato tuber [71,73], woody tissue [74] Phenol extraction Maize roots [29], hemp roots [70], grape berry cluster [40], fruits (banana, apple, strawberry) [38,39,61], potato tuber [71] TCA/acetone/phenol extraction Leaves (olive, redwood, lemon, etc.) [27,34], posidonia leaf [50], fruits (apple, banana, grape, etc.)…”
Section: Grape Berriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The total protein extraction was modified from TCA/Acetone protein extraction protocol [16] with the first step being defatting using hexane as previously described [34]. Briefly, dry peanut kernels (20 g) of each genotype were frozen in liquid nitrogen and ground to powder and defatted with hexane (10 ml/g dry weight) at -20 o C overnight.…”
Section: Total Protein Extraction and 1-d And 2-d Electrophoresesmentioning
confidence: 99%
“…Among them are isozymes [51], restriction fragment length polymorphisms (RFLP), random amplified polymorphisms (RAPD), amplified fragment length polymorphisms (AFLP), and simple sequence repeats (SSR) [24][25][26]30]. Singh et al [48,49] and Bianchi-Hall et al [3] found very limited or no variation among cultivated peanut based on seed protein profiles, Liang et al [34] detected measurable variation between Spanish and runner type peanuts using two-dimensional (2-D) electrophoresis.…”
Section: Introductionmentioning
confidence: 99%